IMPACT OF MATERNAL ATTITUDES AND BELIEFS ABOUT VACCINATION ON NEWBORN IMMUNITY: A PROSPECTIVE COHORT STUDY (The Research of Medical Science Review, 2024)
This prospective cohort study examines the impact of maternal attitudes and beliefs about vaccination on newborn immunity at Swat Medical College and Allied Teaching Hospitals from 2022 to June 2024. A total of 300 pregnant women were recruited and their vaccination beliefs assessed using a structured questionnaire. Newborn immunity was evaluated by measuring antibody levels against key vaccine-preventable diseases at 6 months of age. The study found that positive maternal attitudes towards vaccination were significantly associated with higher antibody levels in newborns (p < 0.01). Additionally, factors such as maternal education, previous vaccination experiences, and exposure to vaccination information positively influenced maternal attitudes. These findings highlight the critical role of maternal beliefs in shaping newborn immunity and underscore the importance of targeted educational interventions to promote vaccination awareness among expectant mothers. This research provides valuable insights for public health strategies aimed at improving immunization rates and enhancing newborn health outcomes